L’élaboration d’un dictionnaire bilingue des valeurs mobilières - Lavoie, Judith (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
As of today, one cannot find, in Canada, a dictionary totally dedicated to securities. The concept of securities refers to a large sphere that includes preferred shares and partnerships, as well as fraud and broker dealers. This paper will analyze the making of a bilingual dictionary of securities through four different steps: 1-the literature on the subject; 2-the nomenclature; 3-the microstructure; 4-the bilingual lexicon and the medium. At each of these steps, the following objectives will be followed: first, to compile the Canadian terminology which applies to securities; second, to offer to researchers, translators and professionals a lexicographical tool that is complete and useful; and third, to take into account, if need be, the legal aspects of the terms defined.